Therapeutic Communities in new asylum settings - Ferrazza, Daniele de Andrade; Sanches, Raphael Rodrigues [UNESP]; Rocha, Luiz Carlos da [UNESP]; Justo, Jose Sterza [UNESP] (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2017)
Even with insufficient evidence, it is possible to realize that the National Politics on Mental Health clearly proposes overcoming an old asylum design that it was marked for centuries the service to the population. However, the expansion of hospitalizations in therapeutic communities for the treatment of chemical dependencies can be considered a step back in Brazilian anti-asylum fight. This present paper aims to study from a standpoint of genealogical inspiration, the hospitalizations in therapeutic communities with special attention to its relations with the history of asylum imprisonment and population biopolitics control. Thus, in opposition to the Movement of Psychiatric Reform, the hospitalization in therapeutic communities, which follow the prohibitionist logic and moralizing conceptions, have been shown like a major biopolitics strategies of exclusion, segregation and sanitation for the assortment and control of urban concentrations.
Keywords: Psychiatric reform; Therapeutic Communities; Chemical dependencies